O USO DE SIMULADORES COMPUTACIONAIS NOS PROCESSOS DE ENSINOAPRENDIZAGEM DE ELETRICIDADE: UM ESTUDO COM ALUNOS DA TERCEIRA SÉRIE DO ENSINO MÉDIO - Martins, Carlos Alberto Gomes (2008)
Computer simulators are technological tools that can help teachers to lead, guide and encourage controlled teaching-learning situations, pedagogically interesting for the level of education they want. From a pedagogical point of view, computer simulators are useful and simple softwares, since lead students to interact with them, as they facilitate the understanding of abstract concepts, laws and characteristics of the physical world. In this study, it was aimed to plan and develop a sequence of activities of learning based on strategy of computer simulation for the conceptual field of Electricity in the perspective to the Vergnaud s Theory of Conceptual Fields, and evalu ate it from the analysis of opinion of students in third grade of high school forward the implementation of these activities. For the sequence of activities, resources from the Web, computer, and computer simulators available in the literature are used. The concepts present in physical activities are electric charge, electric force, electric field and electric potential. For the evaluation of proposed activities, it were used questionnaires, the diary sheets of activities and the teacher s diary of field. The participants were students of the third series of Teaching Middle of Escola Estadual de Educação Básica Manoel, of the city of Manoel Viana, RS. The questionnaires were submitted to an analysis of content. The results indicate that the sequence of activities developed for the teaching of Electricity, based on computer simulators, presents itself as a potential tool for the promotion of teaching and learning of Physics. The sequence of proposed activities and the diary sheets of activities seem to motivate the students for learning Physics by making lessons more interesting, helping them to understanding the abstract concepts involved in this conceptual field. However, computer simulators in education should be used with care; it was observed that these tools need to be integrated into lessons organized by the teacher, who proved to be a mediator of fundamental importance in monitoring the activities.